Argentine Children's press in the 19th Century - López García, María (2020)
The article is a preliminary investigation of the first Argentine children's magazines in the framework of glotopolitics. This allows to attend to different aspects of those archive items: technical conditions (of printing and distribution available in the period), particularities of the social insertion of the child audience to which these journals were originally intended, and political context of publication (especially the debates on the characteristics that national public education would assume). Finally, the paper investigates the way in which these publications interpret the discussions about what should be the national language (the vehicular language used in school education) and the language used by the written press.